Koszyk świadczeń gwarantowanych - Miaskowski, Jaromir (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: This article presents different way of meaning of benefit health basket package. The Polish system of the health care needs changes and one need the basket for guarantee of the patient basic laws. Thats way the situation they require patient, his wholesome needs, demands on definite services from the side of you to the adjustment. The benefit basket package should make up the rationalization of expenses on the health care and show necessary procedures to saving health and human life. The„basket of medical procedures” institute the great challenge for his creators because of his strategic value in correct functioning the system of the health care.